Assessing Territorial Impacts of the EU Cohesion Policy - Medeiros, Eduardo (2017)
This article examines the territorial impacts of the EU Cohesion Policy in Portugal, between 1990 and 2010, at the national level. To reach some conclusions, after a brief overview of the existing literature on territorial impact assessment (TIA) procedures, we present the main features of a proposed TIA technique, which we called TARGET_TIA, and applied to our study case. This analysis permitted us to go beyond the general scope of the EU Cohesion Policy evaluations, which concentrate mainly on the socioeconomic and environmental dimensions, by placing on evidence other key-territorial dimensions, such as Territorial Governance/Cooperation and Polycentricity. Findings indicate that, in general, the EU Cohesion Policy had positive territorial impacts in Portugal, namely by supporting the construction of absent and necessary physical infrastructures. However, the lack of spatial planning and strategic vision limited a more effective and efficient use of Cohesion Funds in Portugal